Care coordination for adults and older people: The role and contribution of the non-statutory sector. Issue 5 (17th October 2016) - Abendstern, Michele; Jasper, Rowan; Loynes, Nik; Hughes, Jane; Sutcliffe, Caroline; Challis, David
Abstract : Purpose: The purpose of this paper is to provide new insights into the contribution and experiences of non-statutory sector (voluntary) services delivering care coordination. Design/methodology/approach: This qualitative study, based on face-to-face semi-structured interviews with 17 managers from a range of non-statutory sector services, used thematic data analysis supported by a framework approach. Findings: Four themes emerged: commissioning arrangements undermined non-statutory sector development; working relationships between statutory and non-statutory services required time and energy to navigate and sustain; the establishment of a niche role in the larger network of provision; and tensions relating to future developments. The non-statutory sector was found to provide a mix of services, including specialist provision targeting specific communities that complemented or substituted for those provided by the state. Managers wanted their services to be recognised by the statutory sector as equal partners in the delivery of care coordination and were also keen to retain their independence. Practical implications: Findings provide information for service commissioners and managers from statutory and non-statutory sectors indicating a complex set of experiences and views regarding the role of the latter. This is particularly salient in a political landscape which has increasing expectations of their involvement in the provision of care coordination. Originality/value: This study considers the work of the non-statutory sector in the delivery of care coordination to adults and older people, an area under-reported to date. It suggests that there are opportunities available for these services to become embedded within a wider social care system and to excel by retaining or developing specialist roles and services.